"Can You Imagine What's Happened in Durham?": Duke University and a New University–Community Engagement Model. Issue 1 (2nd January 2021) - Ehlenz, Meagan M.
Abstract: Problem, research strategy, and findings: As Durham's (NC) economy collapsed in the mid-1990s, Duke established a plan to intervene. Its actions aligned with anchor institution models at many universities; its approach, however, was unique. In a city where Duke was a fixture, university leadership understood a top-down approach was not viable. Instead, administrators launched a community-led model intended to change the "story [from] 'Look at what Duke did', to 'Can you imagine what's happened in Durham?'" according to one administrator in a 2015 interview. I use a longitudinal case study to examine Duke's anchor institution model in 12 Durham neighborhoods. I consider Duke's approach from the mid-1990s to present, drawing from interviews with Duke administrators, community organizations, and neighborhood representatives; newspaper articles and reports; and a descriptive analysis of neighborhood change. I explore an anchor model that engages nonprofit partners and community development strategies. My findings show the potential for a multipartner anchor model that cultivates neighborhood improvement and minimizes (to an extent) gentrification pressures that can arise from anchor investment. Duke's anchor model offers a unique perspective on university–community engagement, partnerships, and neighborhood investment. Takeaway for practice: Duke's case offers insights for how major institutions—from university anchors to local government—can recast their roles in communities; it also offers a roadmap for how institutions can engage (and benefit) neighborhoods in meaningful ways. Informed by a collaborative anchor model, Duke empowered residents to identify their own neighborhood priorities and partnered with local community organizations to meet those aims. This anchor model reveals a powerful role for intermediaries, including planners and community organizers, to connect institutional resources with neighborhood priorities. Supported by a participatory planning process, there are opportunities to realign anchor institution strategies and tools with neighborhood priorities to move toward mutually beneficial outcomes.